The Influence Of Perception, Motivation And Financial Rewards On Accounting Students' Career Interest In Become Public Accountants - Eldad; Antong; Usman, Halim (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of perception, career motivation, and financial rewards on accounting students' career interest in becoming Public Accountants at the University of Muhammadiyah Palopo. This study uses a quantitative method to analyze the relationship between the independent and dependent variables. The sampling technique uses the Slovin formula. The results show that career motivation and financial rewards have a significant effect on accounting students' career interest in becoming Public Accountants, while perception does not have a significant effect on accounting students' career interest in becoming Public Accountants. These findings indicate that motivational factors and financial incentives play an important role in attracting accounting students' career interest in becoming Public Accountants. This study provides insights that can be used in developing educational strategies and policies for the accounting profession, particularly in shaping students' interest in the Public Accounting profession.